(3eZfi GddHjH Yf cJH GdCYGQjHs - (3LeGd GdOjf CHh YHO Gddg Hf CHj gTGe GdCfUGQjs
(3ChdgG (B:s
(3bGd GdTjN Hf gTGe GdCfUGQi CeG HYO aEf Chdi eG JbJQMg GdbQGjM eG jJjSQ Hg age cJGH GdefRd hjJVM Hg eYfi MOjK fHjg GdeQSd , aEfgeG GdhSjdI Edi GdSYGOI GdCHOjI GdHGH GdChd ai JaSjQ GdeaQOGJ hPcQ CMcGegG s
(3BNQgG (B:s
(3hGdYGTQ EYWGA CaYGd ai GdJYLH Mce CaYd GdJaVjd ai LhGR GdJUZjQ hPdc CeKdI cKjQI hgPG BNQ eG JjSQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1751s
Keywords: (3GdfMhs